The Role of Individuals in Organisations: A Systematic Literature Review on Workplace Behaviour and Performance - Setyawati, Ira; Wardani, Yusnita; Sopiah (Jurnal Ilmu Manajemen, 2025)
Individuals play a crucial role in shaping organisational dynamics, influencing workplace behaviour, job performance, and overall organisational success. This study conducts a Systematic Literature Review (SLR) to examine recent research on the impact of individual factors, such as motivation, job satisfaction, leadership perception, and organisational commitment, on workplace outcomes. Using the PRISMA framework, relevant studies published between 2015 and 2024 were identified from databases such as Scopus. The findings indicate that individual behaviours significantly affect team collaboration, innovation, and organisational effectiveness. Additionally, leadership styles, organisational culture, and employee well-being play a mediating role in enhancing job performance and engagement. The review also highlights emerging trends such as remote work, digital transformation, and employee adaptability in the modern workplace. Future research should explore the long-term impact of evolving work environments on individual contributions. This study provides valuable insights for organisations seeking to optimise employee performance and foster a productive work culture.